Disease-Associated Dopamine Receptor D2 Variants Exhibit Functional Consequences Depending on Different Heterotrimeric G-Protein Subunit Combinations - Nele Niebrügge; Olga Trovato; Roman Praschberger; Andreas Lieb (Biomedicines, 2024)
Background: Dopamine receptors (DRs) are G-protein-coupled receptors (GPCRs) found in the central nervous system (CNS). DRs are essential for mediating various downstream signaling cascades and play a critical role in regulating the dopaminergic nigrostriatal pathway, which is involved in motor control. Recently, mutations in DRD2 (WT), p.Ile212Phe (I212F), and p.Met345Arg (M345R) have been associated with hyperkinetic movement disorders and shown to alter heterotrimeric G-protein complex signaling and β-arrestin recruitment. Methods: To conduct a detailed investigation of the I212F and M345R functional phenotypes, we used the TRansdUcer PATHway (TRUPATH) assay to study heterotrimeric G-protein recruitment and the Parallel Receptorome Expression and Screening via Transcriptional Output (PRESTO-Tango) assay to evaluate transcriptional activation following arrestin translocation for β-arrestin recruitment. Results: In our study, we could confirm the reported mutant’s loss-of-function phenotype in β-arrestin 2 recruitment (reduced agonist potency and decreased maximal signaling efficacy in comparison to the WT). However, a detailed analysis of basal/constitutive activity also revealed a gain-of-function phenotype for mutant M345R. For a more comprehensive investigation of heterotrimeric G-protein complex signaling, we investigated the impact of WT mutants in combination with (i) a specifically suggested assay, and (ii) the most abundantly expressed heterotrimeric G-protein complex combinations in WT receptor-enriched regions. We were able to confirm the reported gain-of-function phenotype by Rodriguez-Contreras et al. and extend it by the use of the most abundant heterotrimeric G-protein subunits, GαoA and Gαi1, β1 and β2, and γ3 and γ7, in mouse and human basal ganglia. Conclusions: Although our results indicate that the interaction of the two variants with the most highly expressed heterotrimeric G-protein complex subunit combinations also results in a gain-of-function phenotype, they also clearly demonstrate that the phenotype can be significantly altered, dependent on heterotrimeric G-protein complex expression.